Control of Dengue Vector by the Sterile Insect Technique Considering Logistic Recruitment - Esteva, L.; Yang, H.M. (Trends in Computational and Applied Mathematics, 2006)
We propose a mathematical model to assess the effects of irradiated male insects introduction in a previously infested region, taking into account the logistic recruitment of sterile male insects. The release of sterile male insects aims to displace gradually the natural (or wild) insect from the habitat. We discuss the suitability of this release technique when applied to peridomestic adapted Aedes aegypti mosquitoes which are transmitters of Yellow Fever and Dengue disease.